1986
DOI: 10.1159/000242506
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Acidosis and Hypoxia on Intestinal Blood Flow of Sheep Fetus

Abstract: In sheep fetuses 110–130 days of age acidosis (blood pH 6.95; produced by infusion with 1.1 M lactic acid) significantly lowered blood flow (ml/min/100 g) to the full thickness wall of the jejunum from 135 ± 11 to 93 ± 14 and in the full thickness wall of the ileum from 122 ± 13 to 95 ± 11. The decrease was mainly due to the decline in blood flow to mucosa of the segment, where flow decreased from 182 ± 20 to 83 ± 14 in the jejunum and from 130 ± 10 to 107 ± 9 in the ileum. Fetal hypoxemia (PaO2 of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1989
1989
2001
2001

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…It is known, for instance, that organ weights are disproportionately affected in IUGR (15), but its effects on the structural development of specific organs have received little attention. The development of the gastrointestinal tract is likely to be affected by placental insufficiency, as the blood supply to the gut is known to be reduced during fetal hypoxia (16)(17)(18) , and it has been shown that mucosal blood flow is affected most (19). Intrauterine growth retardation induced by restriction of maternal protein intake has been shown to result in retarded gastrointestinal development in rats (10,20,21), and it was of interest to determine if similar changes accompanied growth retardation induced by restriction of placental function in fetal sheep.…”
mentioning
confidence: 99%
“…It is known, for instance, that organ weights are disproportionately affected in IUGR (15), but its effects on the structural development of specific organs have received little attention. The development of the gastrointestinal tract is likely to be affected by placental insufficiency, as the blood supply to the gut is known to be reduced during fetal hypoxia (16)(17)(18) , and it has been shown that mucosal blood flow is affected most (19). Intrauterine growth retardation induced by restriction of maternal protein intake has been shown to result in retarded gastrointestinal development in rats (10,20,21), and it was of interest to determine if similar changes accompanied growth retardation induced by restriction of placental function in fetal sheep.…”
mentioning
confidence: 99%